2000
DOI: 10.1210/jcem.85.5.6552
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Stimulation of Corticotropin-Releasing Hormone Gene Expression Requires a Cyclic Adenosine 3′,5′-Monophosphate Regulatory Element in Human Primary Placental Cytotrophoblast Cells*

Abstract: Production of placental CRH, which is identical to the peptide synthesized and secreted in the hypothalamus, has been linked to human parturition. Glucocorticoids stimulate placental CRH secretion and messenger ribonucleic acid expression, in contrast to their inhibition of CRH synthesis in the hypothalamus. A positive feedforward loop involving glucocorticoid-CRH-ACTH-glucocorticoid is thought to drive the exponential increase in placental CRH leading to delivery. Tissue-specific effects of glucocorticoids on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Although the CRH gene and mRNA of pCRH and hypothalamic CRH appear identical (Arbiser et al, 1988;Frim et al, 1988), their regulation is tissue specific. In contrast to the inhibitory influence of glucocorticoids on expression of the CRH gene in the hypothalamus, glucocorticoids activate the promoter region in the placenta and stimulate the synthesis of CRH (Cheng et al, 2000;Robinson et al, 1988). The difference in behavior of the CRH gene in the placenta and hypothalamus is due to the expression of different transcription factors, co-activators and corepressors in these two tissues (King et al, 2002).…”
Section: The Hpa Axis In Pregnancy and Postpartummentioning
confidence: 99%
See 1 more Smart Citation
“…Although the CRH gene and mRNA of pCRH and hypothalamic CRH appear identical (Arbiser et al, 1988;Frim et al, 1988), their regulation is tissue specific. In contrast to the inhibitory influence of glucocorticoids on expression of the CRH gene in the hypothalamus, glucocorticoids activate the promoter region in the placenta and stimulate the synthesis of CRH (Cheng et al, 2000;Robinson et al, 1988). The difference in behavior of the CRH gene in the placenta and hypothalamus is due to the expression of different transcription factors, co-activators and corepressors in these two tissues (King et al, 2002).…”
Section: The Hpa Axis In Pregnancy and Postpartummentioning
confidence: 99%
“…The difference in behavior of the CRH gene in the placenta and hypothalamus is due to the expression of different transcription factors, co-activators and corepressors in these two tissues (King et al, 2002). In vivo and in vitro studies have documented that glucocorticoids stimulate the production of CRH mRNA and protein from placental cells in a dose-response manner (Cheng et al, 2000;Glynn et al, 2007;King et al, 2001;Sandman et al, 2006). This positive feedback loop results in dramatic elevations of maternal ACTH, cortisol and pCRH across gestation (see Fig.…”
Section: The Hpa Axis In Pregnancy and Postpartummentioning
confidence: 99%
“…Glucocorticoids exert a negative feedback effect on CRH in the hypothalamus, and it has been shown that dexamethasone is able to reduce cAMP stimulation of the CRH promoter by more than 50 percent in transiently transfected AtT20 cells (47). Conversely, in the placenta glucocorticoids act to increase both basal and cAMP stimulated CRH promoter activity in transfected human primary placental cells (47).…”
Section: Role Of Glucocorticoidsmentioning
confidence: 99%
“…The glucocorticoid dependent stimulation of CRH in the placenta does not appear to involve the GR binding sites which mediate glucocorticoid repression of CRH activity in the AtT20 cells (33). A study to locate the region required for dexamethasone stimulation of CRH in the placenta, using transfections of luciferase reporter constructs containing progressive 5' deletions of the human CRH gene into cultured human primary placental cells, found that deletion of the region between -342 and -213bp resulted in loss of the dexamethasone responsiveness (47).…”
Section: Role Of Glucocorticoidsmentioning
confidence: 99%
“…In particular, while glucocorticoids inhibit hypothalamic production of CRH, they stimulate placental production. This stimulatory effect occurs via the cyclic AMP response element in the CRH promoter (Cheng et al ., 2000). The exponential rise observed in corticotrophin‐releasing hormone during pregnancy may well be driven by a positive feed forward circuit involving glucocorticoid production (Karalis et al ., 1996).…”
mentioning
confidence: 99%